O uso do blog no ensino e aprendizagem da microbiologia - Silva, Elisângela Jeronima Inácia Andrade (2015)
This work is educational product a blog that provides experiments with alternative materials in teaching and learning of microbiology as well as videos that discuss about the microbial world. This research is justified by the need for a "tool" where one can find experiments with alternative materials in microbiology content. The aim of this study is to provide a virtual space where teachers can find experiments with alternative materials. As for the methodology it is a mixed research, quantitative as to the form answered by teachers in order to trace the profile of teachers through the use of new technologies and qualitative compared to comments made by teachers in relation to experiments and videos. The research shows that teachers seek to improve towards new technologies, through the blog a sociocultural interaction was possible, since there was socialized communication between teachers on the use of experimental activities in the classroom as well as in relation to videos on the microbial world about the videos on the microbial world.